Environment and Sustainable Economic Development: Approach to Environmental Problems - Gaur, Amitosh (JOURNAL OF INDUSTRIAL RELATIONSHIP CORPORATE GOVERNANCE AND MANAGEMENT EXPLORER, 2022)
The concept of “environment” has evolved as a global issue in the early 1970s. At first, it was a kind of global recognition that the Earth‟s ecosystems are in fact fragile, and that human beings have been contributing much to its degeneration. When countries started to join efforts to strike a balance between improving the quality of human life and protecting the environment for the sake of future generations, a new awareness materialized. The social and economic welfare of human beings is closely linked to their environment. Any change in the socioeconomic fields will have an impact on the earth‟s environment and vice versa, whether positively or negatively, immediately or eventually. And in many cases, negative results are irreversible.. Keywords: environment, Economic, whether positively human life